Exploring Online RN-to-BSN Student Perceptions of Learner Presence. Issue 2 (March 2020) - Olson, Christina; Benham-Hutchins, Marge
Abstract: AIM: The aim of this study was to describe how RN-to-BSN student and program-specific characteristics influence student perceptions of learner presence (LP) in the online learning environment. BACKGROUND: Online RN-to-BSN students represent a diverse group of practicing nurses who must balance multiple obligations and challenging learner requirements. LP represents the student's perceptions of being close to and interacting with faculty and peers within the online learning environment. METHOD: A descriptive, exploratory design was used to examine the relationship between participant perceptions of LP and student and program characteristics. RESULTS: Findings describe student and program characteristics and perceptions of LP. Significant findings revealed that more collaborative assignments were associated with higher perceptions of LP; individual assignments resulted in lower perceptions. CONCLUSION: This study may enhance faculty understanding of this population of students and the extent to which course activities impact students' communication and collaboration to meet online learner requirements. Abstract : Supplemental digital content is available in the text.